A multi-modal exploration of heterogeneous physico–chemical properties of DCIS breast microcalcifications. Issue 8 (21st March 2022) - Gosling, Sarah; Calabrese, Doriana; Nallala, Jayakrupakar; Greenwood, Charlene; Pinder, Sarah; King, Lorraine; Marks, Jeffrey; Pinto, Donna; Lynch, Thomas; Lyburn, Iain D.; Hwang, E. Shelley; Grand Challenge PRECISION Consortium,; et al.
Abstract : Combined crystallographic and spectroscopic methods were used to investigate the heterogeneity of breast calcifications found associated with ductal carcinoma in situ, revealing distinctive patterns in protein distribution and mineral composition. Abstract : Ductal carcinoma in situ (DCIS) is frequently associated with breast calcification. This study combines multiple analytical techniques to investigate the heterogeneity of these calcifications at the micrometre scale. X-ray diffraction, scanning electron microscopy and Raman and Fourier-transform infrared spectroscopy were used to determine the physicochemical and crystallographic properties of type II breast calcifications located in formalin fixed paraffin embedded DCIS breast tissue samples. Multiple calcium phosphate phases were identified across the calcifications, distributed in different patterns. Hydroxyapatite was the dominant mineral, with magnesium whitlockite found at the calcification edge. Amorphous calcium phosphate and octacalcium phosphate were also identified close to the calcification edge at the apparent mineral/matrix barrier. Crystallographic features of hydroxyapatite also varied across the calcifications, with higher crystallinity centrally, and highest carbonate substitution at the calcification edge. Protein was also differentially distributed across the calcification and the surrounding soft tissue, with collagen and β-pleated protein features present to differing extents. Combination of analytical techniques in this study was essential to understand the heterogeneity of breast calcifications and how this may link crystallographic and physicochemical properties of calcifications to the surrounding tissue microenvironment.